Just Jerry : how drawing shaped my life : a memoir - Pinkney, Jerry (Little, Brown and Company, Hachette Book Group, 2023)
"Jerry Pinkney, Caldecott Medal winner and illustrator of over one hundred books, tells the story of his childhood and how he developed his artistic talent"--